‘The Brick’ is not a brick: a comprehensive study of the structure and dynamics of the central molecular zone cloud G0.253+0.016 - Henshaw, Jonathan D.; Ginsburg, A.; Haworth, T. J.; Longmore, S. N.; Kruijssen, Diederik; Mills, E. A. C.; Sokolov, V.; Walker, D. L.; Barnes, A. T.; Contreras, Y.; Bally, J.; Battersby, C.; et al. (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. In this paper we provide a comprehensive description of the internal dynamics of G0.253+0.016 (a.k.a. ‘the Brick’); one of the most massive and dense